High annual-cycle repeatability suggests low flexibility to environmental changes in a near-threatened migratory shorebird - Schwemmer, Philipp; Donnez, Marie; Mercker, Moritz; Garthe, Stefan; Boschert, Martin; Düttmann, Heinz; Elts, Jaanus; Fartmann, Thomas; Fiedler, Wolfgang; Jiguet, Frédéric; Kämpfer, Steffen; Korniluk, Michał; et al. (Springer Nature, 2026)
Migratory species often repeat spatio-temporal patterns within their annual cycle. Although this may help to promote knowledge about local features and site quality, stereotyped behaviours may also create an ecological trap by preventing the flexibility required to adjust to environmental changes. Using a long-term international dataset, this study assesses 24 spatial and temporal parameters describing the repeatability of the entire migratory cycle in 94 individuals of the migratory near-threatened Eurasian curlew (Numenius arquata) that were tracked for up to 7 consecutive years using high-resolution GPS tags. Twenty-two parameters show significant repeatability, with the highest repeatability for use of the same breeding and wintering sites, indicating consistent faithfulness. All migration and stopover parameters during spring migration are also significantly repeatable, with lower repeatability for autumn migration, likely related to variable breeding success. The location of migration routes varies between consecutive years, but intra-individual similarity is significantly greater than inter-individual similarity. While the potential of adaptations to long-term environmental changes needs further studies (preferably including several cohorts of individuals) there are indications of a potentially maladaptive behaviour to short-term changes that should be carefully observed by site managers to conserve this near-threatened species.
Keywords: animal behaviour; animal migration; phenology